Batteries that go with the flow. - Patel, P. (IEEE spectrum)
If we're ever to run our electric grid on the on-again, off-again power that wind and sun provide, we're going to need better batteries. About half a dozen types of batteries are now grid-ready, but a 30-year-old technology known as a flow battery could be the best bargain.